Effect of certain metrological parameters on the extension of urgent protective action zone in Tehran research reactor accidents. (January 2022) - Pooya, S.M. Hosseini; Hosseinipanah, M.; Adeli, R.
Abstract: In a core melting accident of a reactor, the release of radioactive material into the environment is inevitable. The amount of effective dose received by people around these facilities and consequently the urgent protective action zone (UPZ) strongly depend on the climatic conditions at the time of the accident and afterwards. In this study, the effect of wind speed, air stability class, temperature, and rainfall on the total effective dose equivalent (TEDE) at different time/place intervals of a hypothetical partial core melt accident around a research reactor was investigated using simulation method. The results showed that the stability class E, warm temperature, and light rain could lead to the highest dose of individuals. In addition, very low wind speeds were recommended for the facilities located in cities with high density of high-rise buildings and/or tropical areas in this regard. Highlights: Core melt accident of research reactors lead to release of radioactive material. Urgent protective action zone (UPZ) strongly depend on the climatic conditions. Stability class E, warm seasons, and light rain are the worst case for UPZ. Low wind speeds in tropics with high-rise buildings are important in UPZ. Mixing layer height in regions with a prevailing cold climate should be considered.